A study of the clinical profile of 50 patients of COPD with correlation between clinical, radiological and spirometric evaluation - Kamdar, Deepali J.; Patel, Dharmesh Kumar (International Journal of Research in Medical Sciences, 2017)
Background: Chronic obstructive pulmonary disease (COPD) is a common, preventable and treatable disease that is characterised by persistent respiratory symptoms and airflow limitation that is due to airway and/ or alveolar abnormalities usually caused by significant exposure to noxious particles or gases. Tobacco smoking, occupational exposure to organic and inorganic dusts, chemical agents and fumes and biomass cooking are the risk factors for COPD. Chronic dyspnoea, cough, sputum production, wheezing and chest tightness are the common symptoms of COPD. The present study was undertaken to evaluate the clinical, radiological and spirometric parameters in patients with COPD and to demonstrate a correlation between them. Methods: This was a prospective study of 50 patients of COPD who presented to out- patient department. We included all patients above 40 years of age with a smoking index of 200 or more, or history of exposure to occupational dust, biomass fuel gas or exposure to other obnoxious gases; and who had history of dyspnoea and cough. Spirometry was performed to confirm the diagnosis and to grade the severity of airflow obstruction. History of dyspnoea, cough, sputum production, wheezing, chest tightness, fever, weight loss and the number of exacerbations in the previous year was noted. We then performed a detailed clinical examination. Blood was sent for haemogram and arterial blood gas analysis and all patients underwent an ECG, 2- D Echo and HRCT of the thorax. We then studied the correlation between the clinical, radiological and spirometric profiles in these patients. Results: Out of the 50 patients, majority was between 50-59 years of age, with male to female ratio of 1.94:1.00. History of smoking was present in 74% patients, exposure to biomass fuel in 12% and exposure to occupational dust in 6% patients. Commonest symptom was dyspnoea (in 100% patients) followed by cough (88%), sputum production (68%), wheezing (58%), chest tightness and fever (30%) and weight loss (28%). HRCT was positive in 75% patients, while ECG changes were seen in 42% patients and pulmonary hypertension was present in 54% patients. A significant association was observed between grade 5 dyspnoea on mMRC, hypoxia, hypercarbia, pulmonary hypertension and Gold-5 airflow obstruction. Conclusions: In the present study of 50 cases, COPD was seen predominantly in male patients, with a mean age of presentation between 50- 59 years. Tobacco smoking was the commonest etiological factor. Clinical symptoms most commonly documented were dyspnoea, cough with or without expectoration, wheezing, chest tightness, fever and weight loss. A significant association was observed between grade 5 dyspnoea on mMRC, hypoxia, hypercarbia, pulmonary hypertension and Gold-5 airflow obstruction.